1995
DOI: 10.1063/1.468969
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared femtosecond photoionization/dissociation of cyclic aromatic hydrocarbons

Abstract: Pulses of 780 nm light of duration 170 fs and power densities up to 3.8ϫ10 13 W cm Ϫ2 are used to study the photoionization/dissociation processes in the series of gas phase, cyclic aromatic hydrocarbons including benzene, naphthalene, phenanthrene, and anthracene. The near-infrared ionization process leads to the production of intact molecular ions for all of the molecules studied. Measurements of the ion intensity as a function of laser fluence revealed the order of the ultrafast ionization process to be 8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 21 publications
5
91
0
Order By: Relevance
“…The aims of the experiment determine the choice of laser parameters. FLMS has been shown to be useful for analysis due to its efficiency in producing dominant parent molecular ions, particularly in the IR wavelength regime, in agreement with DeWitt et al 28,29 Less relative fragmentation is observed at IR compared to UV wavelengths, an effect which is common to all the molecules studied by the Glasgow group. Other groups have also recognised the potential of FLMS, especially in the analysis of organometallic molecules.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The aims of the experiment determine the choice of laser parameters. FLMS has been shown to be useful for analysis due to its efficiency in producing dominant parent molecular ions, particularly in the IR wavelength regime, in agreement with DeWitt et al 28,29 Less relative fragmentation is observed at IR compared to UV wavelengths, an effect which is common to all the molecules studied by the Glasgow group. Other groups have also recognised the potential of FLMS, especially in the analysis of organometallic molecules.…”
Section: Discussionmentioning
confidence: 57%
“…An intense femtosecond laser (up to 4 Â 10 14 W cm À2 , and 50-90 fs) was used to probe the samples in a time-of-flight mass spectrometer at wavelengths of 750 and 375 nm. This is an order of magnitude increase in laser intensity over recent measurements by DeWitt et al 28,29 Of particular interest is the question of whether the soft ionization reported above continues into this higher intensity regime and if double ionization reported by Smith et al 17 for benzaldehyde is also apparent for these molecules.…”
Section: à2mentioning
confidence: 80%
See 1 more Smart Citation
“…[7][8][9] The possibility of intact molecular ion formation by femtosecond laser pulses was identified in 1995. 10) However, it is evident that intact molecular ion formation is not always possible when utilizing the fundamental wavelength of a conventional Ti:Sapphire laser. We have identified a key factor to the formation of intact molecular ions.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrashort intense laser pulse has led to the observation of many interesting strong field phenomena in atoms and molecules including bond-softening and hardening [1], above threshold ionization and dissociation [2,3], intact ionization of large polyatomic molecules [4], transient field-induced resonance [5] and adiabatic passage of light-induced potentials [6]. Most of these phenomena can be quantitatively understood using the concept of light-dressed potential energy surfaces [7].…”
Section: Introductionmentioning
confidence: 99%